ENGLISH VOCABULARY BUILDING DIFFICULTIES AT ISLAMIC BOARDING SCHOOL: PROBLEMS AND SOLUTIONS - Arsyad, Ulya Sari; Samtidar, Samtidar; Baa, Sultan (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study aims at finding out the aspects that affect Islamic Boarding School students’ English vocabulary building difficulties and how to solve the difficulties. The study employed mixed method (QUAN-qual) explanatory design to achieve the objectives of the research. Questionnaire and interview were used to collect data. The participants of the questionnaire were one class (33) of Seventh Grade students of Holistic Boarding School of Darul Arqam Muhammadiyah Makassar, and 10 students were taken as interview participants by purposive sampling technique. The result of the research showed that there are three aspects be the most of difficulties faced by the students, namely: grammar, connotation, and pronunciation. The data also showed that the students used dictionary, practice with friends, and searching on internet to solve those difficulties.Keywords: Students’ difficulty, Vocabulary, Solve.